Transformational leadership with rahmatan lil ‘alamin in university born of social enterprises - Mhd. Sarif, Suhaimi; Ismail, Yusof; Azan, Zaliza (Pusat Pengembangan Integrasi Ilmu Naqli & Aqli (PIINA), 2017)
Recently, higher education institutions (HEIs) have began to actively engage in community relations by establishing social enterprises. The social enterprises have in fact become of HEIs’ financial sustainability agenda within the community-industry-university-government mandate. While the mandate can be coined with multiple objectives, they may be summed up as the HEIs’ responsibility to extend mercy to the world (rahmatan lil ‘alamin).